An undergraduate research experience: Synthesis, modification, and comparison of hydrophobicity of zeolites A and X. (16th August 2016) - Giroux, Michael; Sahadeo, Emily; Libera, Robert; Maurizi, Ashley; Giles, Ian; Marteel-Parrish, Anne
Graphical abstract: The focus of this research was to delineate a method to increase the hydrophobicity of zeolites A and X. Functionalization of the zeolites with silane ligands of various sizes was explored in depth. Infrared spectroscopy, SEM, TGA and a macroscopic evaluation aided in the final characterization. Abstract: Two procedures using a template-free synthesis of zeolites A and X were compared in an effort to assess how modification of the porous structure of zeolites with various ligands impacts the property of hydrophobicity. Modification with ligands such as octyltrichlorosilane (OTCS), dichlorodiphenylsilane (DCDPS), chlorotrimethylsilane (CTMS), hexamethyldisiloxane (HMDS) as well as with a combination of CTMS and HMDS, was performed. Both procedures led to the formation of water repellant materials. The hydrophobicity of zeolite A increased when zeolite A was modified with DCDPS and with OTCS. Zeolite X demonstrated superior hydrophobic properties when modified with all ligands, except with HMDS. Infrared spectroscopy (IR), macroscopic analysis, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA) data are presented.